Short-chain fatty acids and type 2 diabetes: a bibliometric analysis of knowledge structure, research hotspots, and future directions - Zheng, Likun; Jiang, Rongsheng; Fang, Jinxu; Tan, Yi; Wang, Yan; Li, Lian; Liu, Mingjun (Frontiers in Microbiology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a public health challenge that urgently needs to be addressed globally. Short-chain fatty acids (SCFAs), as metabolic products of gut microbiota, have increasingly attracted attention for their role in the pathogenesis of T2DM. This study employs bibliometric and visual analysis methods, aiming to systematically depict the knowledge structure, research hotspots, and future directions in this field.MethodWe screened 965 publications on SCFAs and T2DM from the Scopus and Web of Science Core Collection databases. Visual analysis was conducted by using tools such as VOSviewer and CiteSpace.ResultSince 2016 publications in this field have increased rapidly. China leads in publication volume, while the United States plays a central role in collaboration and academic influence. Key contributors include Max Nieuwdorp and Fredrik Bäckhed. King's College London shows strong academic impact, and Nature is the most influential journal. Keyword analysis highlights the importance of “gut microbiota,” “metabolomics,” “microbial metabolism,” “insulin resistance,” and “dietary intervention.” These topics suggest future research will focus on signaling pathways, personalized nutrition, and microbial interventions.ConclusionsThe current research focuses on a deep exploration of the role and mechanism of SCFAs in T2DM, and it aims to transition from basic research to clinical research. In terms of application, clinical workers are shifting from macroscopic dietary intervention to more precise dietary formulation strategies. The development of technologies such as metabolomics is expected to provide more powerful support for basic research and promote further progress in this field.